Prevalence of Mansonella ozzardi among riverine communities in the municipality of Lábrea, State of Amazonas, Brazil - Jansen Fernandes Medeiros; Victor Py-Daniel; Ulysses Carvalho Barbosa (Revista da Sociedade Brasileira de Medicina Tropical, 2011)
INTRODUCTION: Estimate the prevalence of Mansonella ozzardi infection and calculate the parasitic infection rate (PIR) in simuliid black flies in the municipality of Lábrea, State of Amazonas, Brazil. METHODS: Prevalence was measured using the thick blood smear method collected from the fingers and was related to age, sex and occupation. Simuliidae were collected with a suction apparatus, then stained with hematoxylin and dissected to verify the PIR. RESULTS: The average prevalence rate of M. ozzardi among the 694 individuals examined was 20.7%. Infection was higher in men (27.6%) than in women (14.3%) (p < 0.001) and occurred in most age groups, with the highest prevalence in the following age groups: 38-47 (40%), 48-57 (53.1%) and >58 (60.5%). The highest prevalence rates were observed in the retired (64%), followed by farm workers (47.1%). Infection by M. ozzardi was only identified in Cerqueirellum amazonicum (Simuliidae) with a PIR of 0.6%. CONCLUSIONS: This study showed a high prevalence of M. ozzardi in the riverine communities of Lábrea due to the lack of policies regarding the treatment of microfilaremic individuals in the region and an abundance of competent vectors for M. ozzardi.